INTERSEPSI DAN ALIRAN BATANG TANAMAN KOPI DENGAN BERBAGAI NAUNGAN DI SUMBERMANJING WETAN, MALANG - Ni Made Sri Gitalaxmi Mahasidhi; Sugeng Prijono (Jurnal Tanah dan Sumberdaya Lahan, 2021)
The current climate change has an impact on crop production, especially coffee plants. Rainfall is one of the climate elements that influences the process of crop cultivation, because of its role in the availability of water crops. Raindrops that fall on the vegetated land cover does not directly reach to ground, but will temporarily be accommodated by a canopy, stems and plant branch. Once those places saturated with water, the raindrops will drop to the soil surface through the canopy, stem flow and partially evaporated back into the atmosphere that called interception. The study aims to determine the effect of the shade of coffee plants on the interception, and stemflow of plant canopy. As well as knowing the relationship between rainfall with throughfall, stemflow, and interception. This research was conducted at smallholder coffee plantation in Sumbermanjing Wetan District on the use of gamal shade coffee grown, sengon shade coffee grown, and sun-grown coffee. The results showed that the value of canopy throughfall in the three land uses was not statistically significantly different, but there was a tendency for monoculture coffee plants which has a greater yield that is 66,38% of the total rainfall of 15,32 mm. The highest stemflow value is in the sengon shade coffee grown of 3,07% of the total rainfall of 15,32 mm. Interception in the gamal shade coffee grown is the highest compared to other land uses that results obtained are 36,92% of the total rainfall of 17,1 mm. Rainfall has a relationship with the value of stemflow, throughfall and interception. Based on the correlation analysis test the results were significantly correlated with strong relationship.